(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
The accumulation of metals in aquatic organisms is a growing environmental and public health concern, often linked to contamination from industrial and agricultural sources. This study investigated the concentrations of iron (Fe), zinc (Zn), and copper (Cu) in Oreochromis niloticus and Pangasius sp., collected from a commercial fishpond in Marang, Terengganu. Metal concentrations in fish tissues were determined using acid digestion followed by flame atomic absorption spectrophotometry (FAAS). Results showed that Pangasius sp., a bottom-dwelling species, accumulated significantly higher levels of Fe (271 mg/kg), Zn (50.6 mg/kg), and Cu (16.2 mg/kg) as compared to O. niloticus, a column feeder. These differences are likely due to species-specific habitat preferences and feeding behaviours, with Pangasius sp. being more exposed to sediment-associated metals. To evaluate potential human health risks, Target Hazard Quotients (THQs) were calculated, indicating possible non-carcinogenic effects. Importantly, the concentrations of all metals exceeded the permissible limits set by the World Health Organisation (WHO) and the Malaysian Food Act. These findings highlight the need for ongoing monitoring of aquaculture environments and the implementation of effective management strategies to minimise metal contamination and ensure food safety.